Internet a społeczeństwo otwarte - Wieczorek, Marcin (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2005)
The author questions the relations between two developmental aspects of a modern society based on the assumption that Poland faces the necessity of building an information society and an open society. In his opinion an information society cannot be created without the establishment and reinforcement of an open society which would provide the foundations and reference point for the information society. This is not possible unless the attitude to education and knowledge, including the knowledge of the media, changes, particularly in a society that needs to transform within two dimensions and evolve from a rural and industrial society to an information one and from a closed one to an open one. An information society may only be an open one provided that it offers alternative solutions to transactional society and its mass culture.